Aging Influence on Fatigue Characteristics of RAC Mixtures Containing Warm Asphalt Additives - Feipeng Xiao; Wenbin Zhao; Serji N. Amirkhanian (Advances in Civil Engineering)
Aging is an important factor to affect the long-term performance of asphalt pavement. The fatigue life of a typical warm mix asphalt (WMA) is generally related to various factors of rheological and mechanical properties of the mixture. The study of the fatigue behavior of the specific rubberized WMA is helpful in recycling the scrap tires and saving energy in terms of the conventional laboratory aging process. This study explores the utilization of the conventional fatigue analysis approach in investigating the cumulative dissipated, stiffness, and fatigue life of rubberized asphalt concrete mixtures containing the WMA additive after a long-term aging process. The aged beams were made with one rubber type (−40 mesh ambient crumb rubber), two aggregate sources, two WMA additives (Asphamin and Sasobit), and tested at 5 and 20ºC. A total of 55 aged fatigue beams were tested in this study. The test results indicated that the addition of crumb rubber extends the fatigue resistance of asphalt binder while WMA additive exhibits a negative effect. The study indicated that the WMA additive generally has an important influence on fatigue life. In addition, test temperature and aggregate source play an important role in determining the cumulative dissipated energy, stiffness, and fatigue life of an aged mixture.